Atomically Dispersed Iron Cathode Catalysts Derived from Binary Ligand-Based Zeolitic Imidazolate Frameworks with Enhanced Stability for PEM Fuel Cells. Issue 7 (9th April 2019) - Zhang, Hanguang; Ding, Shuo; Hwang, Sooyeon; Zhao, Xiaolin; Su, Dong; Xu, Hui; Yang, Haipeng; Wu, Gang
Abstract : Iron-nitrogen-carbon (Fe-N-C) catalysts for oxygen reduction reaction (ORR) have exhibited a great promise to replace current platinum-based catalysts for proton exchange membrane fuel cells (PEMFCs). However, insufficient stability is the major hurdle to prohibit their practical applications. Here, we report a binary ligand strategy to synthesize Fe-doped zeolitic imidazolate framework-8 (ZIF-8) catalyst precursors through combining traditional 2-methyimidazole (mIm) and the secondary imidazolate or triazole-containing ligands. Compared to triazole-based secondary ligands, imidazolate-based ones are able to retain the shape and size of crystal particles from precursors to catalysts during thermal activation, providing great feasibility to control catalyst morphologies. Among studied ligands, integrating 2-undecylimidazole (uIm) as the secondary ligand with mIm enabled atomically dispersed Fe-N-C catalysts with high ORR activity and obviously enhanced durability in acidic electrolytes. Unlike single mIm precursor, using the mIm-uIm binary ligand synthesis, increasing Fe doping content does not result in the formation of Fe-rich aggregates. The unique hollow carbon particle morphology observed with the mIm-uIm derived catalyst leads to increased surface area allowing to accommodate more atomic FeN4 active sites. The increased order of carbon structure in the mIm-uIm derived catalyst is likely beneficial for enhancement of catalyst stability.